Untargeted metabolomics based on GC-TOF-MS reveals the optimal pre-fermentation time for black glutinous rice wine. Issue 1 (1st January 2019) - Mu, Yu; Su, Wei; Yu, Xiao-Ting; Mu, Ying-Chun; Jiang, Li; Wang, Hong-Lin
ABSTRACT: Pre-fermentation is crucial for black glutinous rice wine production. However, the dynamic changes occurring in metabolites during pre-fermentation remain unclear. Hence, multivariate analysis to investigate the relationship between metabolites and fermentation time was performed. Both PCA and OPLS-DA score plots showed a typical drift of metabolite profiles during fermentation for 0–60 h, whereas a reverse change occurred after 60 h. Of the 28 significantly different metabolites (SDMs) (VIP > 1 and p < .05) identified during pre-fermentation, 50% were enriched at 60 h including sugar, phenolic acid, and organic acid. This resulted in the highest levels of total phenolic and total acid. Pathway analysis based on SDMs indicated that the starch and sucrose metabolism, alanine, aspartate, and glutamate metabolism, and pentose phosphate pathway were most relevant to pre-fermentation (Pathway impact value > 0.1 and p < .05). The integrated metabolic pathway was generated to understand the transformation and accumulation of SDMs. Metabolite profiles at 0, 60, and 72 h were compared using S-plot. More sugar types were observed at 60 h than at 72 h. Moreover, succinic acid and 4-hydroxyphenylethanol, as metabolites of yeast, were significantly upregulated between 60 and 72 h. Therefore, 60 h is potentially optimal for pre-fermentation of black glutinous rice wine. This study rationalizes the pre-fermentation steps vital for black glutinous rice wine production.